Multisensory design in memory research: the £1 coin case in the digital era - Ji, Yijing; Lin, Qianqian; Liu, Zhenghong; Tran, Trung Hieu; Williams, Leon; Simon, Jude; Fan, Yilin (IOS Press, 2025)
This study explores the effects of multisensory memory on memory for everyday objects, with a particular focus on memory for £1 coins. The study delves into the intersection of sensory anthropology, sensory history, and sensory sociology to examine how multisensory experiences affect memory persistence. The study used a dual-task paradigm and cross-modal stimuli to investigate the effectiveness of different sensory combinations in enhancing memory. Post-epidemic era, unlike offline experiences, this experiment utilised an online survey and a variety of media formats including text, images, video, audio and physical objects. The results showed that multisensory interactions significantly improved short-term memory recall over single-sensory modalities, while visual elements such as colours and shapes had a lasting effect on long-term memory. The study also highlights the potential of multisensory engagement in educational environments and museum experiences, gathering reliable data for future projects in which computers simulate human behaviour.
Keywords: 46 Information and Computing Sciences; 4608 Human-Centred Computing; Behavioral and Social Science; 1.1 Normal biological development and functioning